Protein Extraction Of Locust (Locusta Migratoria) Via Acid Method - Khairul Affendi, Nurul Haziqah (Universiti Sains Malaysia, 2021)
Edible insects have been shown to be high in protein content and a potential solution to encountered food and nutrition insecurity. However, the overall acceptance of entomophagy, or the practice of consuming insects, is not common in some regions due to increasing adoption of modern foods, changed social structures and changes in demography. Locusts (L. migratoria) could be one of an alternative protein source from edible insects because they are highly nutritious and “halal’ to eat for for Muslim market. The aim of this study is to analyze the optimum extraction methodologies for solubilisation of protein from locusts (L. migratoria) powder using acid method. The method of lipid extraction using ethanol followed by protein extraction was carried out using ascorbic acid as an acidic medium. Locusts sourced from Shondong, China contained a high amount of protein. It was divided by two fractions; insoluble locust fraction and a supernatant fraction during the protein solubilization